Enforcing the peace : learning from the imperial past - Marten, Kimberly Zisk, 1963- (New York : Columbia University Press, 2004)
Anarchy makes it easy for terrorists to set up shop. Yet the international community has been reluctant to commit the necessary resources to peacekeeping -- with devastating results locally and around the globe. This daring new work argues that modern peacekeeping operations and military occupations bear a surprising resemblance to the imperialism practiced by liberal states a century ago. Motivated by a similar combination of self-interested and humanitarian goals, liberal democracies in both eras have wanted to maintain a presence on foreign territory in order to make themselves more.
Peace, or change? -- Peacekeeping and control -- State interests, humanitarianism, and control -- Political will and security -- Military tasks and multilateralism -- Security as a step to peace.
Includes bibliographical references (pages 167-192) and index.
Print version record.
JSTOR
Keywords: Peacekeeping forces; Peace-building.; Imperialism; Consolidation de la paix; Impérialisme.; LAW -- International; POLITICAL SCIENCE -- Security (National & International); Imperialism; Peace-building; Peacekeeping forces